An appraisal of off-line signature verification techniques - Shah, Abdul Salam; Khan, M. N. A.; Shah, Asadullah (MECS Publisher, 2015)
Biometrics is being commonly used nowadays for the identification and verification of humans everywhere in the world. In biometrics humans unique characteristics like palm, finger printers, iris etc. are being used. Pattern recognition and image processing are the major areas where research on signature verification is carried out. Hand written signature of an individual is also unique and for identification of humans are being used and accepted specially in the banking and other financial institutions. The hand written signatures due to its importance are at target for fraudulence. In this paper we have surveyed different papers on techniques that are currently used for the identification and verification of offline signatures.